Land Use Management in Disaster Risk Reduction : Practice and Cases from a Global Perspective - Banba, Michiko (Springer, 2017)
This book provides a wide range of studies on methods of assessing natural disaster risks and reducing those risks in the context of land use. A major benefit of the book is that it presents extensive research and practices from interdisciplinary perspectives through case studies of land use management against various natural disasters. The natural hazards include earthquakes, tsunami, floods, and other disasters, with case studies ranging from urban areas to areas with natural environments such as mountains, coasts, and river systems. By quantitative and qualitative analysis, this work illustrates how interactions between natural and human environments create natural disasters, and how disaster risks can be managed or reduced through methods related to land use. This book also covers a variety of challenges in land use management with sample cases from Asia as well as the United States and Europe. The main purpose is to provide greater insight into studies of natural disaster risks from the perspective of land use and the possibility of non-engineering methods to reduce those risks. This goal can be achieved through management of land use against various natural hazards in diverse environments.
Keywords: Land use.; Environmental management.; Natural disasters -- Research.; elektronické knihy; electronic books